A Escola Municipal de Belas Artes de Caxias do Sul : histórias e memórias (1949 a 1967) - Costa, Liliane Maria Viero (My University, 2014)
The Municipal School of fine arts of Caxias do Sul: stories and memories (1949 to 1967) dissertation, investigated the history of the Municipal School of fine arts of Caxias do Sul in the period between the years of 1949, the year of its creation, and 1967, when it was, along with other colleges, incorporated to form the University of Caxias do Sul. The central objective of the research is to narrate a significant part of its building process and dynamic organization, from its institutionalization until its establishment as an institution and its development. The Cultural History bases the analyses produced from diverse documents, found dispersed in a set of locations and collections, such as newspapers, photos, reports and minutes, which helps to compose the tessitura of this study. Therefore, the methodological procedures were documental analysis. A certain chronology has been chosen to describe the historical process. The study was divided into three chapters. The first chapter tells how the city of Caxias do Sul was formed, how its immigration process contributed to the understanding of cultural issues, education, art and the pursuit of modernization. It could be identified two things in this process. First, the arrival of the colonizers and their ingenuity that it wouldn’t be so difficult to establish in the new land .The other was that realizing the difficulties, the fighting spirit guaranteed their survival in this new land. The second chapter presents the movements around the foundation of the school, its protagonists, the city as a receptacle of this space and the receptivity of the population, the presence of a very large administrative politic force. The school was not "embraced" by the Church. Was the municipality that has created its own legislation, respecting the specificities of identified School of art. In the third chapter the EMBA becomes a higher level course and, besides participating in the Constitution of the University of Caxias do Sul, takes a key role in irradiation of art and culture in Caxias do Sul. The EMBA was welcomed and encouraged by the society that understood it as relevant. Participation in school and the teaching of art were considered as differential in the construction of knowledge. The EMBA represents the memory of a part of the history of education in Caxias do Sul, higher education in particular. The creation of an educational institution of art stimulated the access and enjoyment to the universe of art in the mid-20th century in Caxias do Sul.
A dissertação A Escola Municipal de Belas Artes de Caxias do Sul: histórias e memórias (1949 a 1967) conta parte da história da Escola Municipal de Belas Artes de Caxias do Sul no período compreendido entre os anos de 1949, ano de sua criação, a 1967, quando foi, juntamente com outras faculdades, integradas para compor a Universidade de Caxias do Sul. O objetivo central da pesquisa foi o de narrar uma parte significativa de seu processo de criação e dinâmica de organização, a partir de sua institucionalização, seu estabelecimento como instituição e desenvolvimento. Na tessitura do estudo, a História Cultural fundamentou teoricamente as análises produzidas a partir de documentos diversificados, encontrados dispersos em um conjunto de locais e acervos, tais como jornais, fotografias, relatórios e atas. Portanto, os procedimentos metodológicos foram os da análise documental. Na organização da escrita optei por escrever o processo histórico seguindo certa cronologia. O estudo foi dividido em três capítulos. O primeiro capítulo narra como a cidade de Caxias do Sul se constituiu, aspectos do processo imigratório que contribuíram para a compreensão das questões culturais da cidade, a educação e a arte e a busca da modernização. Identifiquei dois sentimentos neste processo. Um na chegada do colonizador e, portanto a ingenuidade de que não seria tão difícil o estabelecimento na nova terra e outro que ao perceber as dificuldades o espírito de luta e conquista garantiu a sobrevivência nesta nova terra. O segundo capítulo apresenta os movimentos em torno da fundação da escola, seus protagonistas, a cidade como receptáculo deste espaço e a receptividade da população, a presença de uma força política administrativa muito grande. A escola não foi “abraçada” pela Igreja. Foi a Prefeitura Municipal que criou legislação própria, identificou, respeitando as especificidades do ensino da arte. No terceiro capítulo a EMBA se torna um curso de nível superior e, além de participar na constituição da Universidade de Caxias do Sul, assume papel fundamental na irradiação da arte e da cultura em Caxias do Sul. A EMBA foi bem acolhida e estimulada pela sociedade que a entendeu como pertinente. A participação na escola e o ensino da arte foram considerados um diferencial na construção dos saberes. A EMBA representa a memória de uma parte da história da Educação em Caxias do Sul em especial o ensino superior. A criação de uma instituição de ensino de arte estimulou o acesso e a fruição ao universo da arte na metade do século XX em Caxias do Sul.
Keywords: Escola de Belas Artes de Caxias do Sul; Ensino superior - Caxias do Sul (RS); Arte - Estudo e ensino; Educação - História; Education; Art, Higher Education